Effects of leading-edge separation on the vortex shedding and aerodynamic characteristics of an elongated bluff body. Issue 206 (November 2020) - Duan, Guiyue; Laima, Shujin; Chen, Wenli; Li, Hui
Abstract: Wind-tunnel experiments were conducted on an elongated bluff body to investigate the effects of leading-edge separation on its vortex shedding and aerodynamic characteristics. Solid wind barriers of various heights were fixed at the leading edge to adjust the flow separation and reattachment. The flow field, particularly the upper-surface boundary layer, was investigated by employing a high-resolution particle image velocimetry (PIV) system. According to the PIV results, it was found that the critical height-to-thickness ratio for the leading-edge separated flow to reattach to the surface is h/t  ​= ​0.5. The streamwise length of the reverse flow region increases with an increase in the height of the wind barrier. The effects of leading-edge separation on the vortex evolution and shedding were analysed. As h/t  ​≤ ​0.5, the leading-edge separated shear layer is stable and reattaches to the surface. There exists only Karman vortex shedding in the wake when h/t  ​≤ ​0.2, while the vortex evolution becomes random when 0.3 ​≤ ​ h/t  ​≤ ​0.5. However, when h/t  ​> ​0.5, the leading-edge separated shear layer becomes unstable, thus resulting in free vortex shedding, convecting downstream, and interacting with the lower shear layer. Moreover, the Strouhal number of the vortex in the wake decreases from h/t  ​= ​0 to h/t  ​= ​0.5 and then increases from h/t  ​= ​0.6 to h/t  ​= ​1.0. Highlights: The effects of leading-edge flow separation on the vortex shedding and aerodynamic characteristics are investigated. The increase of the streamwise length of the inverse flow region depends on the flow reattachment. Vortex shedding and convection from the separated shear layer show different modes, depending on flow reattachment. The Strouhal number decreases from h/t  ​= ​0 to h/t  ​= ​0.5 and then increases from h/t  ​= ​0.6 to h/t  ​= ​1.0.